Disability-Adjusted Life Years for the COVID-19 Pandemic in the Mexican Population - Salinas-Escudero, Guillermo; Toledano-Toledano, Filiberto; García-Peña, Carmen; Parra-Rodríguez, Lorena; Granados-García, Víctor; Carrillo-Vega, María Fernanda (Frontiers in Public Health, 2021)
Mexico is one of the countries most affected by the COVID-19 disease. Although there is vast information on the disease, there still unknown data on the pandemic's societal and economic cost. To estimate this impact, the disability-adjusted life year (DALYs), can be a useful tool. Objective. To assess the DALYs due to COVID-19 in Mexico. Methods. We used the data released by the Mexican Ministry of Health to estimate the DALYs by the sum of the years of life lived with disability (YLDs), and the years of life lost (YLLs). Results. A total of 1,152,885 confirmed, and 324,570 suspected cases of COVID-19 have been registered. Half of the cases were men, with a median age of 43.4±16.9 years. About 8.3% died. A total of 39,202 YLDs attributable to COVID-19. The total YLLs caused by COVID-19 was 2,126,222. A total of 2,165,424.5 DALYs for COVID-19 was estimated. The total DALYs were the highest in people between 50 to 59 years. The DALYs for each COVID-19 case were the highest in individuals between 60 and 79 years. Conclusion. The DALYs generated by the COVID-19 represent a more significant disease burden than that reported for other causes, such as the 2009 H1N1 influenza pandemic. Although it impacts all age groups in terms of disability, the most affected group are people over 50 years of age, whose risk of death is higher.